Psychopathological characteristics of behavioral responses in the context of long-term psychiatric outcomes after mechanical thrombectomy for thrombotic occlusion: an analysis of aggression and hostility - Regush, Андрій (Psychosomatic Medicine and General Practice, 2026)
Objective. To establish the long-term psychiatric consequences of mechanical thrombectomy for thrombotic occlusion. Materials and Methods. A prospective study of 129 patients was conducted between 2022 and 2025 at the Center of Interventional Neuroradiology of the Municipal Non-Profit Enterprise "Kyiv City Clinical Hospital No. 1" (Kyiv, Ukraine) and the Department of Interventional Neuroradiology of the State Institution "Main Medical Clinical Center of the Ministry of Internal Affairs of Ukraine" (Kyiv, Ukraine). The mean age of the participants was $68.4 ± 11.4$ years. The assessment of psychiatric outcomes was performed during the late postoperative period, specifically on the 30th–35th day following thrombectomy. To achieve the study’s objective, a comprehensive methodology was employed: anamestic, clinical-psychopathological, psychodiagnostic, and statistical methods. The psychodiagnostic method was implemented using the Symptom Checklist-90-Revised (SCL-90-R) by Leonard Derogatis (as adapted by S. Dembitskyi and Yu. Sereda, 2015). Results. The study revealed a predominance of the somato-affective component within the structure of psychological distress. The highest severity levels ("severe" and "very severe") were recorded on the scales of somatization (98.4% of patients), anxiety (92.2%), and depression (89.1%). Clinically, these manifestations included hypochondriacal fixation on bodily sensations, vital anxiety centered on the fear of stroke recurrence, and a "crisis of awareness" accompanied by depressive affect and apathy. The Global Severity Index indicated a significant severity of the condition in 74.4% of the examined patients. Conclusions. It was established that the long-term psychiatric consequences of thrombectomy are characterized by the formation of "post-thrombectomy distress syndrome" with a somato-affective dominance. The primary clinical features include hypervigilance toward somatic signals, fear of a recurrent vascular catastrophe, and decreased rehabilitation motivation. The results justify the necessity of implementing a personalized psychocorrection system tailored to the individual distress profile. Keywords: ischemic stroke, mechanical thrombectomy, psychiatry, depression, anxiety. УДК 616.89-008.45/.47:616.831-005.1-089.87]-036.8-085.851